Competitive Adsorption of Phenol, Copper Ions and Nickel Ions on to Heat-Treated Bentonite - Fawzi Banat; Sameer Al-Asheh; Leena Abu-Aitah (Adsorption Science & Technology)
Industrial effluents often contain a mixture of organic and inorganic pollutants. Since the degree of removal of any solute might be affected by the presence of the other, it is important to study the competitive adsorption of these solutes. Batch experiments were carried out to study the competitive adsorption of binary combinations of phenol, copper and nickel compounds in aqueous mixtures on to heat-treated bentonite. The uptake of phenol was not affected by the presence of copper or nickel ions. However, the uptake of copper and nickel decreased in the presence of phenol. In a system that only contained both metal ions in solution, the adsorption capacity of nickel was depressed to a greater extent than that of copper. The pH of the solution strongly affected the adsorption capacity of copper in the phenol/copper system.